Immunogenicity and efficacy of DNA/MVA HIV vaccines in rhesus macaque models - Lynette Siv Chea; Rama Rao Amara (Taylor & Francis Group, 2017)
Introduction: Despite 30 years of research on HIV, a vaccine to prevent infection and limit disease progression remains elusive. The RV144 trial showed moderate, but significant protection in humans and highlighted the contribution of antibody responses directed against HIV envelope as an important immune correlate for protection. Efforts to further build upon the progress include the use of a heterologous prime-boost regimen using DNA as the priming agent and the attenuated vaccinia virus, Modified Vaccinia Ankara (MVA), as a boosting vector for generating protective HIV-specific immunity. Areas covered: In this review, we summarize the immunogenicity of DNA/MVA vaccines in non-human primate models and describe the efficacy seen in SIV infection models. We discuss immunological correlates of protection determined by these studies and potential approaches for improving the protective immunity. Additionally, we describe the current progress of DNA/MVA vaccines in human trials. Expert commentary: Efforts over the past decade have provided the opportunity to better understand the dynamics of vaccine-induced immune responses and immune correlates of protection against HIV. Based on what we have learned, we outline multiple areas where the field will likely focus on in the next five years.